Method for coating slurry on surface of sintered neodymium-iron-boron substrate, preparation method of sintered neodymium-iron-boron magnet and slurry

By coating the slurry of specific viscosity on the surface of the sintered NdFeB matrix and performing heat treatment, the problem of uneven magnet performance is solved, and the uniformity of magnet weight gain and magnetic properties are improved.

CN120236878APending Publication Date: 2025-07-01BEIJING ZHONG KE SAN HUAN HI TECH

Patent Information

Application Number
CN202311873552.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

In mass production, in the prior art, when the slurry is applied to the surface of the sintered NdFeB matrix by roller coating, the performance differences between the magnets are large, resulting in uneven magnetic properties.

Method used

A slurry containing heavy rare earth element powder, organic solvent and binder with a viscosity of 2000 to 5000 mPa.s was used to form a coating layer on the surface of the sintered NdFeB substrate by a roller coating machine, and drying, vacuum heat treatment, grain boundary diffusion and aging treatment were carried out.

Benefits of technology

The magnet weight gain uniformity in and between batches has been achieved, the magnetic performance is more uniform, and the coercive force is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120236878A_ABST
    Figure CN120236878A_ABST
Patent Text Reader

Abstract

The invention provides a method for coating slurry on the surface of a sintered neodymium-iron-boron matrix, a preparation method of a sintered neodymium-iron-boron magnet and the slurry. The method for coating the surface of the sintered neodymium-iron-boron substrate with the slurry comprises the steps that the slurry is prepared; wherein the slurry comprises powder containing heavy rare earth elements, an organic solvent and a binder, and the viscosity of the slurry is 2000-5000 mPa.s; and coating the surface of the sintered neodymium-iron-boron substrate with the slurry by adopting a roller coater to form a coating layer. The slurry provided by the invention is low in viscosity, good in flowability, low in thixotropy, low in shear viscosity mutation rate and low in temperature sensitivity, the weight gain uniformity of magnets in each batch and between batches is good, and the coercive force is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of permanent magnets, and specifically, relates to a method for coating a slurry on the surface of a sintered neodymium iron boron substrate, a preparation method of a sintered neodymium iron boron magnet, and a slurry. Background Art

[0002] Sintered neodymium iron boron magnets are currently regarded as functional materials necessary for energy conservation and performance improvement, and their application scope and production volume are expanding year by year. In order to improve the magnetic properties of the magnets and reduce the usage of heavy rare earths, a grain boundary diffusion process can be adopted, such as preparing a coating of heavy rare earths (such as pure metals, oxides, hydrides, fluorides, and fluoroxyfluorides of Tb or Dy) and coating it on the surface of the sintered neodymium iron boron magnet, and through diffusion treatment, the heavy rare earth elements diffuse from the surface of the sintered magnet along the inside of the magnet.

[0003] CN116417210A discloses a powder slurry for grain boundary diffusion and a magnet manufacturing method. A slurry containing heavy rare earth powder and UV monomer is coated on the surface of a neodymium iron boron substrate, and a coating is formed on the magnet surface by means of photocuring, and then vacuum heat treatment, grain boundary diffusion treatment, and aging treatment are carried out to obtain a high-performance sintered neodymium iron boron magnet. Among them, the coating method can be any one of spraying, slurry dipping, screen printing, roll coating, and spin coating.

[0004] CN106158347A discloses a method for preparing an R-Fe-B type sintered magnet. A slurry containing heavy rare earth powder RX, organic solid powder EP, and organic solvent ET is coated on the surface of the substrate. After drying treatment, an organic thin film layer is formed on the surface of the substrate. After grain boundary diffusion heat treatment and aging treatment, a high-performance magnet is formed, and its coating method is divided into brush coating or roll coating, dipping or spraying according to the shape of the substrate.

[0005] However, when the slurry in the above technical solution is coated on the surface of the substrate by roll coating in mass production, there are significant differences in the performance between the magnets obtained.

[0006] The content in the background art part is only the technology known to the inventor and does not of course represent the prior art in this field. Summary of the Invention

[0007] In order to solve the above technical problems, the present application provides a slurry for a sintered neodymium iron boron substrate. The slurry includes a powder containing heavy rare earth elements, an organic solvent, and a binder, and the viscosity of the slurry is 2000 - 5000 mPa·s.

[0008] In some embodiments of the present application, the powder containing heavy rare earth elements is selected from one or more of heavy rare earth metals, hydrides of heavy rare earth elements, oxides of heavy rare earth elements, fluorides of heavy rare earth elements, oxyfluorides of heavy rare earth elements, and alloys of heavy rare earth elements; the heavy rare earth elements are selected from one or more of Dy and Tb;

[0009] The organic solvent includes a first solvent and a second solvent. The first solvent includes one or more of terpineol, butyl acetate, and tributyl phosphate. The second solvent includes one or more of low molecular weight alcohols, low molecular weight esters, and low molecular weight ketones. The number of carbon atoms in the low molecular weight alcohol, the low molecular weight ester, and the low molecular weight ketone is ≤5; preferably, the mass ratio of the first solvent to the second solvent is (1~1):(1~4);

[0010] The binder includes one or more of polyvinyl alcohol resin, polyvinyl butyral resin, polyvinylpyrrolidone resin, and acrylic resin; preferably, the binder includes polyvinyl alcohol resin; more preferably, the end of the molecular chain of the polyvinyl alcohol resin includes amino and / or amide groups, and the side groups of the main chain of the molecular chain of the polyvinyl alcohol resin include butyral groups, hydroxyl groups, and acetoxy groups. The contents of the butyral group, the hydroxyl group, and the acetoxy group are 70~80%, 10~25%, and 5~10% of the total amount of the side groups, respectively.

[0011] In some embodiments of the present application, the slurry further includes a dispersant and a wetting agent;

[0012] Preferably, the dispersant includes one or more of amide organic compounds, polycarboxylate esters, polycarboxylates, polyacrylate resins, and polyacrylate salts. The wetting agent includes silicone oil; more preferably, the silicone oil includes modified silicone oil, and the modified silicone oil includes a polymethylsiloxane or polyethylsiloxane in which part of the side chains are replaced with one or more functional groups including but not limited to amide groups, epoxy groups, carboxyl groups, ester bonds, and ether bonds, and the replacement ratio is 20%~30%;

[0013] Preferably, the slurry further includes an antifoaming agent; more preferably, the antifoaming agent includes a polymethylalkylsiloxane solution with a mass fraction of 40~50wt% or a propylene glycol block polyether.

[0014] In some embodiments of the present application, the content of the powder containing heavy rare earth elements is 60~85wt%, the content of the organic solvent is 5~37wt%, the content of the binder is 2~10wt%, the content of the dispersant is 0~3wt%, the content of the wetting agent is 0~1wt%, and the content of the antifoaming agent is 0~1.5wt%; preferably, the content of the binder is 2~6wt%, the content of the dispersant is 1~3wt%, and the content of the wetting agent is 0.5~1wt%.

[0015] In some embodiments of the present application, the median particle size of the powder containing heavy rare earth elements is 1-10 μm.

[0016] The present application further provides a method for coating a slurry on the surface of a sintered neodymium iron boron substrate, which includes:

[0017] Preparing the slurry; wherein, the slurry is any one of the above-mentioned slurries; and

[0018] Using a roll coater to coat the slurry on the surface of the sintered neodymium iron boron substrate to form a coating layer;

[0019] Preferably, when the weight of the sintered neodymium iron boron substrate ≤ 20 g, the viscosity of the slurry is 2000-3000 mPa·s.

[0020] In some embodiments of the present application, the thickness of the coating layer is 10-50 μm; preferably, when the weight of the sintered neodymium iron boron substrate ≤ 20 g, the thickness of the coating layer is 10-15 μm.

[0021] In some embodiments of the present application, the surface roughness Ra of the sintered neodymium iron boron substrate is 0.2-0.45 μm.

[0022] In some embodiments of the present application, the roll coater includes a coating roll, and the surface roughness Ra of the coating roll is 1-3 μm; preferably, the surface of the coating roll has grooves; more preferably, the cross-section of the grooves is an isosceles trapezoid, an isosceles triangle or an arc.

[0023] In some embodiments of the present application, the roll coater includes a glue coating roll, and the rotation speed of the glue coating roll is 10-50 m / min.

[0024] The present application also provides a method for preparing a sintered neodymium iron boron magnet, which includes:

[0025] Using any one of the above-mentioned methods to coat a slurry on the surface of the sintered neodymium iron boron substrate; and

[0026] Successively performing drying treatment, vacuum heat treatment, grain boundary diffusion treatment and aging heat treatment on the sintered neodymium iron boron substrate having a coating layer on its surface;

[0027] Wherein, the temperature of the drying treatment is 70-200 °C, the time is 10-60 min, the temperature of the vacuum heat treatment is 250-600 °C, the time is 1-10 h; the temperature of the grain boundary diffusion treatment is 800-1000 °C, the time is 2-50 h; the temperature of the aging treatment is 450-600 °C, the time is 1-8 h.

[0028] The slurry provided by this application has low viscosity, good fluidity, low thixotropy, low shear viscosity mutation rate, low temperature sensitivity, good uniformity of magnet weight gain within and between batches, and significantly improved coercivity.

[0029] Additional aspects and advantages of the present invention will be given in part in the following description, become apparent in part from the following description, or be learned through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings constituting a part of this disclosure are used to provide a further understanding of this disclosure. The schematic embodiments and descriptions thereof of this disclosure are used to explain this disclosure and do not constitute an improper limitation to this disclosure.

[0031] Figure 1 It is a process flow diagram for coating a slurry on the surface of a sintered neodymium iron boron substrate provided in an embodiment of this application.

[0032] Figure 2 It is a process flow diagram for preparing a sintered neodymium iron boron magnet provided in an embodiment of this application. DETAILED DESCRIPTION

[0033] In the following, only some exemplary embodiments are simply described. As those skilled in the art can recognize, the described embodiments can be modified in various different ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary in nature rather than restrictive.

[0034] The following disclosure provides many different embodiments or examples for implementing the present invention. To simplify the disclosure of the present invention, the components and settings of specific examples are described below. Of course, they are only examples and are not intended to limit the present invention. In addition, the present invention may repeat reference numerals and / or reference letters in different examples. This repetition is for the purpose of simplification and clarity and does not itself indicate the relationship between the various embodiments and / or settings discussed. In addition, the present invention provides examples of various specific processes and materials, but those of ordinary skill in the art can be aware of the application of other processes and / or the use of other materials.

[0035] In addition, unless otherwise defined, all terms (including technical terms and scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention belongs. It will also be understood that terms, such as those defined in a common dictionary, should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and the present invention, and will not be interpreted in an idealized or overly formal sense unless explicitly defined as such herein.

[0036] Taking into account the measurements discussed and the errors associated with the measurement of a particular quantity (i.e., the limitations of the measurement system), as used herein, "about" or "approximately" includes the stated value and means within an acceptable range of deviation from the particular value as determined by a person skilled in the art. For example, "about" can mean within one or more standard deviations, or within ±30%, ±20%, ±10% or ±5% of the stated value.

[0037] The following, in conjunction with the drawings and embodiments, describes in more detail the specific embodiments of the present invention, so as to better understand the solution of the present invention and the advantages of its various aspects. However, the specific embodiments and examples described below are for illustrative purposes only and are not a limitation of the present invention.

[0038] In the following description, "sintered neodymium iron boron substrate" is abbreviated as "substrate".

[0039] slurry

[0040] As described in the background art, when the slurry in the prior art is coated on the surface of the substrate by roll coating in mass production, there are significant differences in the performance between the magnets produced.

[0041] The inventors found that when the slurry in the prior art is coated on the surface of the substrate by roll coating in mass production, after drying treatment, the weight gain differences on the surfaces of the individual substrates are significant. Due to the differences in the amount of heavy rare earths attached to the substrate surface, this in turn leads to significant differences in the magnetic properties between the individual magnets obtained after grain boundary diffusion treatment and aging.

[0042] During the coating process, in order to ensure that the coating layer on the surface of each substrate contains a certain amount of heavy rare earth powder, the content of heavy rare earth powder in the slurry will be relatively high, that is, the solid content of the slurry will increase, and then the viscosity value will also increase, resulting in a decrease in the leveling property and making it difficult to form a coating with a uniform thickness during roll coating. In particular, for some substrates with a single weight less than 20 g, when the viscosity is too high, the substrate will adhere to the coating roll and thus be carried away by the coating roll. When the viscosity value of the slurry is low, the leveling property of the slurry will increase, but the slurry is not easily adhered to the surface of the coating roll during roll coating, which will also cause the coating layer formed during the roll coating process to be unstable.

[0043] The inventors found that the above technical problems can be solved by comprehensively regulating the slurry system applied to the substrate.

[0044] When the slurry includes a powder containing heavy rare earth elements, an organic solvent, and a binder, and the viscosity of the slurry is about 2000 to 5000 mPa·s, the powder containing heavy rare earth elements can be evenly dispersed in the slurry, and the slurry system is stable. Thus, when coating with a roll coater, a coating layer with uniform thickness can be obtained, and further, the difference in weight gain between magnets in the same batch is small, and the magnetic properties are more uniform.

[0045] Optionally, when the weight of the sintered neodymium iron boron substrate ≤ 20 g, the viscosity of the slurry is about 2000 to 3000 mPa·s. Within this viscosity range, the thickness of the coating layer formed during coating can be more uniform, and thus the obtained magnetic properties are also more uniform.

[0046] Optionally, in the present application, the powder containing heavy rare earth elements is selected from one or more of heavy rare earth metals, hydrides of heavy rare earth elements, oxides of heavy rare earth elements, fluorides of heavy rare earth elements, oxyfluorides of heavy rare earth elements, and alloys of heavy rare earth elements. Optionally, the heavy rare earth elements are selected from one or more of Dy and Tb. Examples of alloys of heavy rare earth elements can be TbCu, TbFe, TbAl, DyCu, DyFe, DyAl, TbCuAl, DyCuAl, TbCoAl, DyCoAl, TbPrCu, DyPrCu, TbPrNdCuAl, DyPrCuAl.

[0047] Optionally, in the present application, the organic solvent includes a first solvent and a second solvent. Optionally, the first solvent includes one or more of terpineol, butyl acetate, and tributyl phosphate, and the second solvent includes one or more of low molecular weight alcohols, low molecular weight esters, and low molecular weight ketones. When the organic solvent is the above-mentioned compound system, the binder can be better dissolved, the obtained slurry is more stable, and it is easy to achieve a coating layer with uniform thickness. Moreover, the above-mentioned compound system of organic solvents can quickly volatilize from the surface of the substrate after slurry coating to cure the film layer.

[0048] Optionally, the number of carbon atoms of the low molecular weight alcohol, low molecular weight ester, and low molecular weight ketone ≤ 5. Optionally, the low molecular weight alcohol is one or more of ethanol, propanol, n-butanol, isobutanol, n-pentanol, tert-pentanol, ethylene glycol, propylene glycol, and butanediol. Optionally, the low molecular weight ketone is one or more of acetone, methyl ethyl ketone, diethyl ketone, and methyl n-propyl ketone. Optionally, the low molecular weight ester is one or more of ethyl acetate, n-propyl acetate, isopropyl acetate, ethyl propionate, and ethyl 2-hydroxypropionate. Optionally, the mass ratio of the first solvent to the second solvent is about (1 to 1):(1 to 4).

[0049] Optionally, in the present application, the binder includes one or more of polyvinyl alcohol resin (PVA), polyvinyl butyral resin (PVB), polyvinylpyrrolidone resin (PVP), and acrylic resin. Using these resins as the binder can make the powder containing heavy rare earth elements have better dispersibility and stability in the slurry.

[0050] Preferably, the binder includes polyvinyl alcohol resin. More preferably, the end of the molecular chain of the polyvinyl alcohol resin includes amino groups and / or amide groups, and the side groups of the main chain of the molecular chain of the polyvinyl alcohol resin include butyral groups, hydroxyl groups, and acetoxy groups.

[0051] The polyvinyl alcohol resin used in the present application is a long-chain polymer. Its molecular structure is a product obtained by the acetalization reaction of polyvinyl alcohol and aldehyde organic compound monomers. Polyvinyl alcohol is obtained by hydrolysis or alcoholysis of polyvinyl acetate (or vinyl acetate). The long-chain molecular structure provides a relatively low glass transition temperature, so that the polyvinyl alcohol resin has good tensile strength and impact strength. Optionally, the grades of the polyvinyl alcohol resin used in the present application are B-98, B-90, B-79, B-76, the weight-average molecular weight ranges from about 20,000 to about 40,000, and the glass transition temperature is from about 60 °C to about 75 °C.

[0052] Optionally, the end of the molecular chain of the polyvinyl alcohol resin used in the present application includes amino groups and / or amide groups, preferably amide groups, and the amino groups and / or amide groups can be at both ends or one end of the molecular chain. Amino groups and amide groups can make the powder containing heavy rare earth elements have better dispersibility and stability in the slurry. In the present invention, by selecting amino groups and / or amide groups at the end of the molecular chain, the powder containing heavy rare earth elements can interact with these characteristic functional groups through active sites or by forming coordination bonds, etc., so that the powder containing heavy rare earth elements has better dispersibility and stability in the slurry.

[0053] Furthermore, the side groups of the main chain of the molecular chain of the polyvinyl alcohol resin may include butyral groups, hydroxyl groups (e.g., vinyl alcohol groups), and acetoxy groups (e.g., vinyl acetate groups). The six-membered cyclic butyral structure can improve the strength of the molecular chain. As the content of butyral groups increases, the solubility, compatibility, and water resistance increase significantly. The hydroxyl structure provides tear strength and good adhesion. As the hydroxyl value increases, the water solubility increases. As the content of acetoxy groups increases, the water resistance of the product increases.

[0054] Optionally, the contents of the acetal group, hydroxyl group, and acetoxy group are about 70-80%, about 10-25%, and about 5-10% of the total amount of side groups, respectively. The group contents described herein refer to the number contents of the groups. At this content, the interaction and cooperation of each group can obtain a slurry with excellent performance. Since polymers generally exist in the form of molecular coils in solvents, molecules are entangled with each other, and polar molecules interact with each other due to polar forces. Under shear, the molecular chains are prone to conformational transformation, disentanglement, molecular chain stretching, etc., increasing molecular plasticity. After the shear force is removed, due to the inherent entropy, the elastic polymer will return to the molecular coil state again. Therefore, most polymer solutions have shear thinning characteristics. By setting the molecular chain side groups to include acetal groups, hydroxyl groups, and acetoxy groups and controlling their respective proportions, especially the low proportion of hydroxyl groups, the present invention can reduce the intermolecular bonding effect (such as coordination effect) with low shear sensitivity, thereby adjusting the thixotropy of the polymer solution.

[0055] Optionally, the slurry further includes a dispersant and a wetting agent. Adding a dispersant and a wetting agent is beneficial to improving the dispersibility of the powder containing heavy rare earth elements in the slurry and the adhesion ability of the slurry. Optionally, the dispersant includes one or more of amide organic compounds, polycarboxylates, polycarboxylic acids, polyacrylate esters, and polyacrylate salts. Examples of amide organic compounds can be oleic acid amide, stearic acid amide, erucic acid amide, oleoyl ethylene glycol amine, etc. Optionally, the wetting agent includes a modified silicone oil. Optionally, the modified silicone oil includes a polymethylsiloxane or a polyethylsiloxane in which part of the side chains are replaced with one or more functional groups including but not limited to amide groups, epoxy groups, carboxyl groups, ester bonds, and ether bonds, and the replacement ratio is 20%-30%.

[0056] Optionally, the slurry further includes an antifoaming agent. Adding an antifoaming agent is beneficial to improving the stability of the slurry during the production process. Optionally, the antifoaming agent includes a polymethylalkylsiloxane solution or a propylene glycol block polyether with a mass fraction of about 40-50 wt%.

[0057] Optionally, in the slurry, the content of the powder containing heavy rare earth elements is about 60-85 wt%, the content of the organic solvent is about 5-37 wt%, the content of the binder is about 2-10 wt%, the content of the dispersant is about 0-3 wt%, the content of the wetting agent is about 0-1 wt%, and the content of the defoaming agent is about 0-1.5 wt%. By regulating the proportional relationship of each component, the powder containing heavy rare earth elements can be evenly dispersed in the slurry, and the slurry system is stable, so that it is easy to achieve a coating with uniform thickness. Moreover, at the above contents, when the slurry is coated on the surface of the sintered neodymium iron boron substrate by a roll coater to form a coating layer, a coating layer with the required thickness can be obtained only by coating once, and the obtained coating layer has a uniform thickness, which simplifies the process and can also obtain a good coating effect. Preferably, the content of the binder is about 2-6 wt%, the content of the dispersant is about 1-3 wt%, and the content of the wetting agent is about 0.5-1 wt%.

[0058] Optionally, in the slurry, the median particle size (D50) of the powder containing heavy rare earth elements is about 1-10 μm. At this particle size, the fluidity of the prepared slurry is better.

[0059] The slurry provided by the present invention has low viscosity, good fluidity, low thixotropy, low shear viscosity mutation rate, low temperature sensitivity, good uniformity of magnet weight gain within and between batches, and significantly improved coercivity.

[0060] Method for coating slurry on surface of sintered NdFeB substrate

[0061] Figure 1 The method for coating the slurry on the surface of the sintered neodymium iron boron substrate provided by an embodiment of the present application is shown, including the following steps S11 and S12.

[0062] S11: Prepare the slurry.

[0063] The composition and related properties of the slurry are as described above and will not be elaborated here.

[0064] S12: Use a roll coater to coat the slurry on the surface of the sintered neodymium iron boron substrate to form a coating layer.

[0065] Optionally, coat the slurry on one surface of the substrate, or coat the slurry on two symmetric surfaces of the substrate.

[0066] As described above, when the weight of the sintered neodymium iron boron substrate ≤ 20 g, the viscosity of the slurry can be about 2000-3000 mPa·s. Within this viscosity range, the thickness of the coating layer formed during coating can be more uniform, and thus the obtained magnetic properties are also more uniform.

[0067] Optionally, the thickness of the coating layer is about 10-50 μm. When the weight of the substrate ≤ 20 g, the thickness of the coating layer can be about 10-15 μm. Within this range, the performance of the subsequent obtained magnet is more excellent.

[0068] Optionally, the surface roughness Ra of the sintered neodymium iron boron substrate is about 0.2-0.45 μm, which is beneficial to the slurry being fully transferred from the roll coater to the substrate surface, making the coating layer on the substrate surface relatively uniform.

[0069] Optionally, the roll coater includes a coating roll, and the surface roughness Ra of the coating roll is about 1-3 μm, which is beneficial to the slurry being fully transferred from the roll coater to the substrate surface, making the coating layer on the substrate surface relatively uniform.

[0070] Optionally, the surface of the coating roll has grooves. Optionally, the cross-section of the grooves is an isosceles trapezoid, an isosceles triangle or an arc. These shaped grooves are beneficial to the slurry being fully transferred from the roll coater to the substrate surface, making the coating layer on the substrate surface relatively uniform.

[0071] In some other embodiments of the present application, the roll coater includes a glue coating roll, and the rotation speed of the glue coating roll can be about 10-50 m / min. At this rotation speed, the slurry can be coated relatively uniformly on the substrate surface.

[0072] The slurry provided by the present application is coated Figure 1 on the sintered neodymium iron boron substrate by the method shown, and a coating layer with relatively uniform thickness can be obtained.

[0073] Preparation method of sintered NdFeB magnet

[0074] Figure 2 The method for preparing a sintered neodymium iron boron magnet provided by the present application is shown, including the following steps S21-S26.

[0075] S21: Prepare a sintered neodymium iron boron substrate

[0076] Smelt the raw materials according to the composition formula, prepare an alloy rapid solidification sheet, perform hydrogenation and dehydrogenation treatment, prepare fine powder by a jet mill, press the powder into a green compact under an orientation magnetic field, and obtain a green magnet after sintering and aging treatment of the green compact. After machining the green magnet, perform pickling, cleaning and drying treatment to obtain a sintered neodymium iron boron substrate. Optionally, the surface roughness Ra of the sintered neodymium iron boron substrate is 0.2-0.45 μm.

[0077] S22: Coat the slurry on the surface of the sintered neodymium iron boron substrate.

[0078] The specific implementation process of this step is as described above and will not be elaborated here.

[0079] S23: Drying treatment.

[0080] The sintered NdFeB substrate with a coating layer on its surface is dried. Optionally, the drying temperature is 70 - 200 °C and the time is 10 - 60 min.

[0081] If both surfaces of the substrate need to be coated with the slurry, after the first surface is coated and dried, the coating and drying steps for the second surface are then carried out. After both surfaces are coated and dried, a coating weight gain test is performed.

[0082] S24: Vacuum heat treatment.

[0083] The dried magnet is subjected to vacuum heat treatment. Optionally, the vacuum heat treatment temperature is 250 - 600 °C and the time is 1 - 10 h.

[0084] S25: Grain boundary diffusion treatment.

[0085] The magnet after vacuum heat treatment is subjected to grain boundary diffusion treatment. Optionally, the grain boundary diffusion treatment temperature is 800 - 1000 °C and the time is 2 - 50 h.

[0086] S26: Aging heat treatment.

[0087] The magnet after grain boundary diffusion treatment is subjected to aging heat treatment. Optionally, the aging treatment temperature is 450 - 600 °C and the time is 1 - 8 h.

[0088] The NdFeB magnet prepared by the above steps using the aforementioned slurry has excellent magnetic properties.

[0089] The following will illustrate the present application with reference to specific embodiments. The numerical values of the process conditions taken in the following embodiments are all exemplary, and their available numerical ranges are as shown in the aforementioned summary of the invention. For process parameters not specifically noted, they can be referred to conventional techniques. Unless otherwise specified, the reagents and instruments used in the technical solutions provided in the present application can be obtained from conventional channels or the market. Unless otherwise specified, the detection methods in the present application are all conventional detection methods in this industry.

[0090] Example 1

[0091] This example prepares a sintered NdFeB magnet, and the specific steps are as follows:

[0092] 1) Prepare the substrate

[0093] Smelt the raw materials according to the formula amount, and its composition is (PrNd) 29.5 Co 0.7 B 0.91 Cu 0.1 Ga 0.1 Zr 0.2 Fe 68.49, an alloy rapid solidification sheet with a thickness of about 0.3 mm was obtained by a conventional rapid solidification method. Then hydrogen decrepitation was carried out, and subsequently it was ground into powder with an average particle size of about 4.2 μm by gas milling. Then the powder was subjected to orientation forming and isostatic pressing in a magnetic field of 2 T and then sintered. The sintering temperature was about 1000 °C and the sintering time was about 8 h. After cooling to about 900 °C, primary aging was carried out for about 3 h, and then after cooling to about 500 °C, secondary aging was carried out for about 5 h to obtain a magnetic blank. After cutting the magnetic blank, a magnet substrate with dimensions of about 50 mm × 20 mm × 4 mm (the 4 mm direction is the orientation direction) was obtained by grinding. After the magnet substrate was pickled with about 0.3 wt% dilute nitric acid solution for about 10 - 50 s, the surface was washed with deionized water, and then dried. 10 substrate samples were taken, and the average surface roughness Ra was measured, as shown in Table 2.

[0094] 2) Preparation of slurry

[0095] In this embodiment, the powder containing heavy rare earth elements is terbium hydride powder. The terbium hydride powder, dispersant, wetting agent, defoaming agent, binder, first solvent, and second solvent are mixed according to the components and contents in Table 1, and fully stirred under the condition of water bath heat preservation at about 35 °C - 70 °C to make the binder fully dissolve, obtaining a slurry. The viscosity of the slurry was measured with a rheometer at about 20 °C and a rotation speed of 10 rpm, as shown in Table 2.

[0096] 3) Slurry coating

[0097] The slurry was coated on one surface of the substrate perpendicular to the orientation direction through a roll coater including a coating roller to form a coating layer. Among them, the thickness of the coating layer was about 15 μm, and the rotation speed of the coating roller was about 20 m / min; the number of substrates to be coated in each batch was 10,000 pieces, and 10 batches were continuously produced. The surface roughness Ra of the coating roller is shown in Table 2.

[0098] 4) Drying treatment

[0099] The coated substrate was placed in a drying oven and dried at about 100 °C for about 30 min to obtain a substrate with a coating layer on the surface. 25 substrate samples were taken from each batch to measure the weight gain, and the extreme difference of the weight gain ratio of the 10 - batch samples to the substrate weight was calculated, as shown in Table 2.

[0100] 5) Heat treatment (vacuum heat treatment, grain boundary diffusion treatment, aging treatment)

[0101] The dried substrate is subjected to vacuum heat treatment for degreasing at about 400 °C, held for about 1 h, then heated to about 950 °C for grain boundary diffusion treatment, held for about 4 h, and then cooled to about 550 °C for aging treatment, held for about 1 h to obtain a neodymium-iron-boron magnet. For each batch, 20 magnet samples are randomly taken to measure the magnetic properties, and the average value and the extreme difference of the difference between the Hcj of the 10 batches of magnet samples and the Hcj of the substrate (hereinafter referred to as the Hcj increase amount, Hcj increase amount = Hcj of the magnet sample - Hcj of the substrate) are calculated, as shown in Table 2.

[0102] Examples 2 to 16

[0103] The preparation processes of Examples 2 to 16 are similar to that of Example 1, but the composition of the slurry, the content of each component, the average surface roughness of the substrate, the surface roughness of the coating roller, etc. are different. See Tables 1 and 2 for details. In addition, the size of the magnet substrate prepared in Examples 11 to 16 is about 40 mm × 20 mm × 3 mm (the 3 mm direction is the orientation direction), and the magnet substrates of the other examples are the same as those of Example 1.

[0104] The viscosity of the slurry, the extreme difference of the weight gain of the 10 batches of samples after drying treatment compared to the substrate weight ratio, the average value and the extreme difference of the Hcj increase amount, etc. are shown in Table 2.

[0105] Comparative Examples 1 to 2

[0106] The preparation processes of Comparative Examples 1 to 2 are similar to that of Example 1, but the composition of the slurry, the content of each component, the average surface roughness of the substrate, the surface roughness of the coating roller, etc. are different. See Tables 1 and 2 for details. The size of the magnet substrate prepared in Comparative Example 1 is the same as that of Example 1, and the size of the magnet substrate prepared in Comparative Example 2 is about 40 mm × 20 mm × 3 mm (the 3 mm direction is the orientation direction).

[0107] The viscosity of the slurry, the extreme difference of the weight gain of the 10 batches of samples after drying treatment compared to the substrate weight ratio, the average value and the extreme difference of the Hcj increase amount, etc. are shown in Table 2.

[0108] Table 1

[0109]

[0110]

[0111]

[0112]

[0113]

[0114]

[0115]

[0116] Note: PVB-1 is Butvar B-79, with 75% butyraldehyde group, 20% hydroxyl group, and 5% acetoxy group; PVB-2 is Butvar B-98, with 82% butyraldehyde group, 10% hydroxyl group, and 8% acetoxy group. Modified silicone oil: contains polydimethylsiloxane, and part of the polydimethylsiloxane is replaced by amide groups, and the replacement ratio is 25%.

[0117] Table 2

[0118]

[0119]

[0120] As shown in Table 2, the slurry provided in this application has low viscosity and good fluidity, and the magnet weight gain uniformity within and between batches is good, and the coercivity is significantly improved.

[0121] As can be seen from Table 1 and Table 2, when the viscosity of the slurry is too high or too low (Comparative Example 1 and Comparative Example 2), the magnet weight gain uniformity within and between batches is poor, and the properties of the magnets are also non-uniform. When there is no dispersant, wetting agent, or only one component of the organic solvent (such as Example 1 and Example 6), the magnet weight gain uniformity is slightly poor, and the improvement degree of the magnet coercivity is also slightly lower. When the surface roughness of the substrate or the surface roughness of the coating roller is not within the preferred range of this application (Example 14 and Example 15), the magnet weight gain uniformity is slightly poor, and the improvement degree of the magnet coercivity is also slightly lower.

[0122] Obviously, the above-mentioned embodiments are only examples for clearly explaining the present invention, and are not limitations on the implementation manners. For those of ordinary skill in the art, other different forms of changes or modifications can be made on the basis of the above description. It is not necessary and impossible to enumerate all the implementation manners here. And the obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A method for coating a slurry on the surface of a sintered neodymium iron boron substrate, characterized in that, Comprising: Preparing a slurry; wherein, the slurry comprises a powder containing heavy rare earth elements, an organic solvent, and a binder, and the viscosity of the slurry is 2000 - 5000 mPa·s; And Using a roll coater to coat the slurry on the surface of a sintered neodymium iron boron substrate to form a coating layer.

2. The method according to claim 1, wherein The powder containing heavy rare earth elements is selected from one or more of heavy rare earth metals, hydrides of heavy rare earth elements, oxides of heavy rare earth elements, fluorides of heavy rare earth elements, oxyfluorides of heavy rare earth elements, and alloys of heavy rare earth elements; the heavy rare earth elements are selected from one or more of Dy and Tb; The organic solvent comprises a first solvent and a second solvent, the first solvent comprises one or more of terpineol, butyl acetate, and tributyl phosphate, the second solvent comprises one or more of low molecular weight alcohols, low molecular weight esters, and low molecular weight ketones, and the number of carbon atoms of the low molecular weight alcohol, the low molecular weight ester, and the low molecular weight ketone ≤ 5; preferably, the mass ratio of the first solvent to the second solvent is (1 - 1):(1 - 4); The binder comprises one or more of polyvinyl alcohol resin, polyvinyl butyral resin, polyvinylpyrrolidone resin, and acrylic resin; preferably, the binder comprises polyvinyl alcohol resin; more preferably, the molecular chain end of the polyvinyl alcohol resin comprises amino groups and / or amide groups, and the side groups of the main chain of the molecular chain of the polyvinyl alcohol resin comprise butyral groups, hydroxyl groups, and acetoxy groups, and the contents of the butyral group, the hydroxyl group, and the acetoxy group are 70 - 80%, 10 - 25%, and 5 - 10% of the total amount of the side groups, respectively.

3. The method according to claim 1, characterized in that, The slurry further comprises a dispersant and a wetting agent; Preferably, the dispersant comprises one or more of amide organic compounds, polycarboxylates, polycarboxylic acids, polyacrylates, and polyacrylate salts, and the wetting agent comprises silicone oil; more preferably, the silicone oil comprises modified silicone oil, and the modified silicone oil comprises a polymethylsiloxane or a polyethylsiloxane in which part of the side chains are replaced with one or more functional groups including but not limited to amide groups, epoxy groups, carboxyl groups, ester bonds, and ether bonds, and the replacement ratio is 20% - 30%; Preferably, the slurry further comprises an antifoaming agent; more preferably, the antifoaming agent comprises a polymethylalkylsiloxane solution with a mass fraction of 40 - 50 wt% or a propylene glycol block polyether.

4. The method according to claim 3, wherein In the slurry, the content of the powder containing heavy rare earth elements is 60 - 85 wt%, the content of the organic solvent is 5 - 37 wt%, the content of the binder is 2 - 10 wt%, the content of the dispersant is 0 - 3 wt%, the content of the wetting agent is 0 - 1 wt%, and the content of the antifoaming agent is 0 - 1.5 wt%; preferably, the content of the binder is 2 - 6 wt%, the content of the dispersant is 1 - 3 wt%, and the content of the wetting agent is 0.5 - 1 wt%.

5. The method according to claim 1, wherein The median particle size of the powder containing heavy rare earth elements is 1 - 10 μm; Preferably, when the weight of the sintered neodymium iron boron substrate ≤ 20 g, the viscosity of the slurry is 2000 - 3000 mPa·s.

6. The method according to claim 1, characterized in that The thickness of the coating layer is 10 to 50 μm; preferably, when the weight of the sintered NdFeB substrate ≤ 20 g, the thickness of the coating layer is 10 to 15 μm.

7. The method according to claim 1, wherein The surface roughness Ra of the sintered NdFeB substrate is 0.2 to 0.45 μm.

8. The method according to claim 1, wherein The roll coater includes a coating roll, and the surface roughness Ra of the coating roll is 1 to 3 μm; preferably, the surface of the coating roll has grooves; more preferably, the cross-section of the grooves is an isosceles trapezoid, an isosceles triangle or an arc.

9. The method according to claim 1, characterized in that The roll coater includes a glue coating roll, and the rotation speed of the glue coating roll is 10 to 50 m / min.

10. A method for preparing a sintered neodymium iron boron magnet, characterized in that, Comprising: Coating a slurry on the surface of a sintered NdFeB substrate by using the method according to any one of claims 1 to 9; And Successively performing drying treatment, vacuum heat treatment, grain boundary diffusion treatment and aging heat treatment on the sintered NdFeB substrate having a coating layer on its surface; Wherein, the temperature of the drying treatment is 70 to 200 °C, the time is 10 to 60 min, the temperature of the vacuum heat treatment is 250 to 600 °C, the time is 1 to 10 h; the temperature of the grain boundary diffusion treatment is 800 to 1000 °C, the time is 2 to 50 h; the temperature of the aging treatment is 450 to 600 °C, the time is 1 to 8 h.

11. A slurry for sintered neodymium iron boron matrix, characterized in that, The slurry includes a powder containing heavy rare earth elements, an organic solvent and a binder, and the viscosity of the slurry is 2000 to 5000 mPa·s.

12. The paste according to claim 11, characterized in that, The powder containing heavy rare earth elements is selected from one or more of heavy rare earth metals, hydrides of heavy rare earth elements, oxides of heavy rare earth elements, fluorides of heavy rare earth elements, oxyfluorides of heavy rare earth elements, alloys of heavy rare earth elements; the heavy rare earth elements are selected from one or more of Dy, Tb, Ho; The organic solvent includes a first solvent and a second solvent, the first solvent includes one or more of terpineol, butyl acetate, tributyl phosphate, the second solvent includes one or more of low molecular weight alcohols, low molecular weight esters, low molecular weight ketones, and the number of carbon atoms of the low molecular weight alcohols, the low molecular weight esters, the low molecular weight ketones ≤ 5; preferably, the mass ratio of the first solvent to the second solvent is (1 to 1):(1 to 4); The binder includes one or more of polyvinyl alcohol resin, polyvinyl butyral resin, polyvinylpyrrolidone resin, acrylic resin; preferably, the binder includes polyvinyl alcohol resin; more preferably, the molecular chain ends of the polyvinyl alcohol resin include amino groups and / or amide groups, and the side groups of the main chain of the molecular chain of the polyvinyl alcohol resin include butyral groups, hydroxyl groups and acetoxy groups, and the contents of the butyral groups, the hydroxyl groups and the acetoxy groups are 70 to 80%, 10 to 25% and 5 to 10% of the total amount of the side groups respectively.

13. The paste according to claim 11, wherein The slurry further includes a dispersant and a wetting agent; Preferably, the dispersant includes one or more of amide organic compounds, polycarboxylate esters, polycarboxylates, polyacrylate esters, and polyacrylate salts, and the wetting agent includes silicone oil; more preferably, the silicone oil includes modified silicone oil, and the modified silicone oil includes polymethylsiloxane or polyethylsiloxane in which part of the side chains are replaced by one or more functional groups including but not limited to amide groups, epoxy groups, carboxyl groups, ester bonds, and ether bonds, and the replacement ratio is 20% to 30%; Preferably, the slurry further includes an antifoaming agent; more preferably, the antifoaming agent includes a polymethylalkylsiloxane solution or propylene glycol block polyether with a mass fraction of 40 to 50 wt%.

14. The paste according to claim 11, characterized in that, The content of the powder containing heavy rare earth elements is 60 to 85 wt%, the content of the organic solvent is 5 to 37 wt%, the content of the binder is 2 to 10 wt%, the content of the dispersant is 0 to 3 wt%, the content of the wetting agent is 0 to 1 wt%, and the content of the antifoaming agent is 0 to 1.5 wt%; preferably, the content of the binder is 2 to 6 wt%, the content of the dispersant is 1 to 3 wt%, and the content of the wetting agent is 0.5 to 1 wt%.

15. The slurry according to claim 11, wherein The median particle size of the powder containing heavy rare earth elements is 1 to 10 μm.

Citation Information

Patent Citations

  • Method for preparing R-Fe-B sintered magnets

    CN106158347A

Cited By

  • Preparation method and application of organic suspension for improving coercive force of sintered neodymium-iron-boron magnet

    CN121641672A

  • Method for preparing organic suspension for increasing coercivity of sintered neodymium-iron-boron magnets and use thereof

    CN121641672B